Pengembangan Media Pembelajaran E-Learning Berbasis Moodle Pada Mata Kuliah Metodologi Penelitian : Studi pada Program Studi Pendidikan Teknik Bangunan, Fakultas Teknik, Universitas Negeri Jakarta - Sittati Musalamah; Hamdi Muhammad; R. Eka Murtinugraha (Jurnal Pensil : Pendidikan Teknik Sipil, 2020)
The aim of this research is to produce Moodle-based E-Learning learning media in the Research Methodology course with the help of Power Point Software, Google Slides and Moodle. This research is a type of Research and Development research using the 4D development model (Define, Design, Development and Dissemination). This study uses a non-test instrument data collection technique that is a questionnaire given to 2 material experts and 2 media experts. The results of the feasibility of learning media products, amounting to 11 learning materials using a Likert scale in the form of a score of 1-5 are as follows: a) The validation results by the material experts obtained a score of 81.54% which is included in the very feasible category; b) Results validation by media experts obtained a score of 78.4% which is included in the feasible category. Based on the results of the feasibility, it can be concluded that the learning media of E-Learning Moodle is appropriate to be used.